woodland and forest - Ambrose, Jamie (London DK Publications, 2017)
From cold coniferous forests to dry deciduous woodland, children can discover everything about trees and the creatures who live in them, including birds, gorillas, butterflies, and many more. Learn about the different types of forests that exist around the world, such as the Amazon Rainforest in South America and mangrove forests in Asia. With exciting activities, including bark rubbing, and plenty of fun facts, Nature Explorers: Woodland and Forest is the perfect book for children curious about forests and woodlands.
Keywords: Science knowledge book